HUBUNGAN ANTARA FASILITAS BELAJAR DAN LINGKUNGAN BELAJAR DENGAN HASIL BELAJAR IPA - Dewi Budi Utami; Tias Ernawati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2017)
The purpose of this research is to know tendency facilities, environment, and result learning of IPA. In a correlative to know relationship facilities, environment, and result learning of IPA, both do together and alone. This research is correlative descriptive especially ex-post facto. Data collecting technique used questionnaire, documentation, and test. Data analyzing technique used double regression analysis, two predictors and then partial correlation. Prerequisite experiment analysis includes normality experiment of propagation and linearity relationship. The sample is all of the population and used population study technique. It can be shown the tendency of facilities and environment of learning is in the high category. The tendency of learning result of IPA is in the very high category. Correlatively is found value of Fcount = 48,922 > with p= 0,05. It means that there is a positive relationship that very significant between facilities and environments learning and result of learning IPA grade of VIII SMP Taman Dewasa in all Kecamatan Umbulharjo Yogyakarta 2015/2016, both do together and alone. Effective contribution from two predictors is 67.14%, learning facilities are 15.95% and learning environment is 51.19%.